PENERAPAN PIJAT OKSITOSIN TERHADAP PENGELUARAN KOLOSTRUM PADA IBU POST PARTUM DI RUMAH SAKIT TK III 04.06.02 BAKTI WIRA TAMTAMA SEMARANG: IMPLEMENTATION OXYTOCIN MASSAGE TO SPERDING COLOSTRUM AT MATTERNAL POST PARTUM AT THE GENERAL HOSPITAL DR. ADHYATMA, MPH SEMARANG - Haizoen Avita Tani; Yuni Astuti (JURNAL KEPERAWATAN SISTHANA, 2019)
Depression Breast milk is the best food for babies, because it contains all the nutrients the ideal amount and composition required by infants. One of the obstacles in the early breastfeeding is the production of breast milk in small quantities on the first day after birth. Ways that can be done toincrease milk production is the oxytocin message. The purpose of case study to improve sepending colostrum at maternal post partum after doing oxytocin message. This type of research is descriptive using a case study approach. Subjects in this study were two patients maternal post partum. The result of the analysis to subject 1 spending colostrum time this is 5.00 hours with fast categori, while to subject 2 spending colostrum time this is 06.20 hours with low categori. Can be concluded there oxytocin message effect on the time spending colostrum.nurse have to apply message oxytocin to the mother post partum to give colostrum on her baby soon after birth.